Features X-ray examinations during endodontic treatment (Эндодонтия Today)
The study of the reliability display of root canals of all groups of teeth was carried out in the laboratory by 158 intraoral radiographs, 36 orthopantomogram, 1434 computer tomography. In clinical studies 127 patients analyzed 374 intraoral periapical x-rays, 47 computer tomographic studies. The results of laboratory and clinical studies have shown that intraoral radiographs and orthopantomogram not objectively shows the structure of the roots of all groups of teeth. These techniques are not in all cases faithfully portray the quality and features of the obturation of root canals. The methodology for the assessment of the structure of the roots of the teeth and spatial location of root canals is cone-beam computed tomography in axial and oblique projections. For objective evaluation of the quality of endodontic treatment informative combination of methods intraoral radiography and cone-beam computed tomography. However, because of the way the image application cone-beam computed tomography does not eliminate the difficulties in the diagnosis of fractures of the roots of the teeth and determine the presence of fragments of endodontic instruments in the root canals.